Застосування поняття «електронна комерція» при побудові системи бухгалтерського обліку - Плотніченко, І.Б. (Культура народов Причерноморья, 2013)
У статті досліджено й систематизовано підходи вчених до трактування понять
«електронна комерція» і «електронна торгівля»: ототожнення, розмежування та змішування цих
понять; здійснено їх критичний аналіз; визначено специфічні з облікової точки зору аспекти фінансово –
господарських операцій у сфері електронної комерційної діяльності; обумовлено вплив змістового
значення електронної комерції на побудову системи бухгалтерського обліку. В статье исследованы и систематизированы подходы ученых к трактовке понятий
«электронная коммерция» и «электронная торговля»: отождествление, разграничения и смешивание
этих понятий; осуществлен их критический анализ; определены специфические с учетной точки зрения
аспекты финансово - хозяйственных операций в сфере электронной коммерческой деятельности;
обусловлено влияние смыслового значения электронной коммерции на построение системы
бухгалтерского учета. The article investigates the academic approaches to the interpretation of the terms «electronic
commerce» and «electronic trade» made their critical analysis, determined by the impact of the essential value
of the electronic commerce on the construction of the accounting system.
Scientific approaches of the interpretation of the terms «electronic commerce» and «electronic trade» of the
author are systematized into three groups.
The scientists belonging to the first approach reduce the essence of the electronic commerce in the process of the
sale of goods through the Internet and the other information and communication technologies.
The proponents of the second scientific approach considering electronic trade as a part of electronic commerce
and differentiate these concepts. The author proves that e-commerce includes not only transactions related to the
trade, but also a number of other activities that determine the specificity of their reflection in the accounting
system.
The researchers attributed to the third approach mix the concept of «electronic commerce» and «electronic
trade», and therefore these categories become somewhat incorrect semantic meaning.
The article outlines the features of the financial - economic transactions in e-commerce that influence the
methodology of the accounting. It is indicated that the specificity of the accounting system makes typology of ecommerce,
including the division of the Internet - commerce: content-commerce, services and trade.
The author states that from the accounting point of view it is a very important division of the electronic
commercial activities into two categories: indirect e-commerce: electronic orders - physical delivery, and direct
e-commerce: orders, delivery, payment of goods and services made "on-line".